Determinan Nilai Perusahaan Manufaktur di Bursa Efek Indonesia - Irma Sari Permata; Mulyadi (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2020)
The purpose of this study is to analyze the company’s micro factors such as liquidity (CR), solvency (DER) as well as macro factors, namely interest rates to firm value (Tobin’Q) so that they can assess the development of good company conditions. The companies studied were manufacturing companies listed on the Indonesia Stock Exchange in period of 2014 – 2018. The method of this research was explanatory research. Samples were taken by purposive sampling from a population of manufacturing companies that met the sample criteria. The analysis used is multiple linear regression analysis. The results showed that liquidity and dividends had a significant positive effect on firm value, while solvency did not support the hypothesis. Implications and suggestions are discussed in the article.